Multi-index analysis of climate change events recorded by loess-paleosol deposits in the upper Hanjiang River valley since MIS 3 - Wentong Zhang; Lansong Lv; Jiayu Lu; Ye Lv; Haiyan Wang; Xu Xu; Jiangli Pang (PLoS ONE, 2026)
The upper Hanjiang River basin has been an important area for human life and production since ancient times. Marine Isotope Stage 3 (MIS 3) is a special period of relatively warm and humid climate during the last glacial period. However, the climate record of MIS 3 in this region, especially the difference of chemical weathering characteristics between this region and the northern Loess Plateau, remains unclear. An in-depth field investigation was conducted in this study on the upper Hanjiang River valley and we found a typical loess-paleosol profile named Tuojiawan (TJW). Multi-proxy indicators including sedimentology, chronology, magnetic susceptibility, grain size, and geochemistry were used to analyze the climate change characteristics. The results show that the stratigraphic consists of fluvial deposits (T 1 -al1), interaction layer (T 1 -al2), Malan loess (L 1-3 ), paleosol (L 1-S2 ), Malan loess (L 1-2 ), paleosol (L 1-S1 ), Malan loess (L 1-1 ), transitional loess (L t ), paleosol (S 0 ), recent loess (L 0 ), and modern soil (MS). The pedogenic intensity varies significantly in different layers and presents a tendency of S 0 > L 1-S2 > L 1-S1 > L t > L 1 (L 1-1 , L 1-2 , L 1-3 ). This indicates that MIS 3 is not a continuously dry and cold stage. TJW profile also showed a phase of gradual shift to warm-wet (11.5–8.5 ka BP), maximum warm-wet period (8.5–3.1 ka BP), and a phase of gradual shift to cool-dry (after 3.1 ka BP). Compared with the records of the Loess Plateau, the chemical weathering intensity of the warm and humid event in the upper reaches of the Hanjiang River in the late MIS 3 is different, which reveals the unique response mode of the region to global climate change and may be controlled by different monsoon subsystems.